2005
DOI: 10.1016/j.ymthe.2005.07.686
|View full text |Cite
|
Sign up to set email alerts
|

Differential Myocardial Infarct Repair with Muscle Stem Cells Compared to Myoblasts

Abstract: Myoblast transplantation for cardiac repair has generated beneficial results in both animals and humans; however, poor viability and poor engraftment of myoblasts after implantation in vivo limit their regeneration capacity. We and others have identified and isolated a subpopulation of skeletal muscle-derived stem cells (MDSCs) that regenerate skeletal muscle more effectively than myoblasts. Here we report that in comparison with a myoblast population, MDSCs implanted into infarcted hearts displayed greater an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
136
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 50 publications
12
136
1
Order By: Relevance
“…30,34 When compared to myoblasts, these cells exhibited an improved ability to restore dystrophin ϩ fibers following injection in mdx muscles. 35 This property was further correlated to their capacity to escape rapid cell death, 30,36 to proliferate after injection, 30 and to escape immune rejection as a result of a low level of major histocompatibility complex class 1 expression. 35 Among their advantages, their ability to self-renew efficiently and their multilineage capacity to differentiate was also reported.…”
mentioning
confidence: 99%
“…30,34 When compared to myoblasts, these cells exhibited an improved ability to restore dystrophin ϩ fibers following injection in mdx muscles. 35 This property was further correlated to their capacity to escape rapid cell death, 30,36 to proliferate after injection, 30 and to escape immune rejection as a result of a low level of major histocompatibility complex class 1 expression. 35 Among their advantages, their ability to self-renew efficiently and their multilineage capacity to differentiate was also reported.…”
mentioning
confidence: 99%
“…Adult stem cells and progenitor cells for mesenchymal lineages from various tissues and organs, such as bone marrow (6), peripheral blood or blood vessels (7), adipose tissue (8), synovium (4), umbilical cord blood (9), and skeletal muscle (10), have been described. For cartilage regeneration and repair, stem cells are an attractive cell source due to their superior capacity for self-renewal, proliferation, and response to stress (11,12). Results of several studies have suggested that various stem cells have potential for cartilage regeneration and repair in experimental cartilage injury models (13)(14)(15).…”
mentioning
confidence: 99%
“…The transplantation led to substantially more muscle mass and higher neovascularization. VEGF can promote myogenesis and vascularization in numerous muscle injuries including cardiac injuries [26]. After ischemic injury to normal mouse skeletal tissue, VEGF expression increased and direct injection of adenovirus VEGF at the site of ischemic injury led to reduced apoptosis as compared with controls that did not receive VEGF [10].…”
Section: Discussionmentioning
confidence: 99%